INVESTIGATING THE ROLE OF CORPORATE SOCIAL RESPONSIBILITY IN ENHANCING BRAND REPUTATION AND CUSTOMER LOYALTY - Supriatna, Ucu (KRIEZ ACADEMY : Journal of development and community service, 2025)
Background : Organizations face an increasingly uncertain environment characterized by crises such as natural disasters, cyberattacks, and economic downturns. These challenges threaten operational stability, making effective crisis management essential for ensuring organizational resilience. Aims : This study aims to explore the role of crisis management strategies in enhancing organizational resilience, identify key factors contributing to resilience, and provide actionable recommendations for improving crisis preparedness and response. Research Method : A mixed-methods approach was employed, combining quantitative surveys of 500 professionals across various industries with qualitative interviews and case studies. Data analysis included statistical correlations and thematic evaluations to provide a comprehensive understanding. Results and Conclusion : The findings highlight the importance of proactive planning, adaptive leadership, effective communication, technological integration, resilient cultures, and strategic external collaborations in navigating crises. Organizations adopting these strategies reported improved recovery times, employee engagement, and stakeholder trust, underscoring the critical link between crisis management and resilience. Contribution : This study contributes to the theoretical understanding of resilience by integrating diverse crisis management strategies and provides practical insights for organizations aiming to strengthen their crisis preparedness and recovery capabilities.